KARAKTERISTIK SIFAT FISIKO KIMIA GELATIN HALAL YANG DIEKSTRAK DARI KULIT AYAM BROILER MELALUI VARIASI SUHU - Puspawati, Ni Made; Simpen, I Nengah; Suciptawati, Ni Luh Putu (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 1 Januari 2014, 2014)
The aim of this study was to characterize physicochemical properties of gelatin extracted from skin of chicken at different temperatures (40 o C, 45 o C, 50 o C) for 24 hours. Pre-treatment of dry defatted skin of chicken was done with a combination of alkaline-acid solution sodium hydroxide (NaOH, 0.15%w/v), sulfuric (0.15%v/v) and citric acid (0.7%w/v) and extraction was carried out in waterbath by adding water at pH 4-5. Physicochemical properties analyzed were yield, gel strength, proximate compositions, pH and characteristicfunctional groups. Statistical analysis showed that temperatures of extraction significantly (p<0.05) affected the physicochemical properties of gelatin produced. The yield and proximate compositions increased by increasing temperatures of extractions.  The highest yield, water, protein, ash and fat content of gelatin   (based on dry weight) were obtained at 50 o C and the lowest at 40 o C. Conversely, gel strength of gelatin decreased by increasing the temperature of extraction. Gelatin prepared at 40 o C showed the highest gel strength (114.84g bloom) which was higher than gel strength of gelatin commercial (98.81 bloom) (p<0.05) while gelatin extracted at 45 o C gave the lowest value (73.44g bloom). Gelatin extracted at different temperatures had significantly different pH (p<0,05). pH value of gelatin extracted at 40 o C,45 o C, dan 50 o C was 3,29, 3,47, and 4,29 respectively. Fourier transform infrared (FTIR) spectra of all gelatin prepared in this experiment revealed the presence of band corresponding to –OH, C-O, N-H and C-N, C=O and NCO of secondary amidewhich characteristic for gelatin functional groups.
Keywords: chicken skin Broiler, gelatin, gel strength, thermal gravimetric analysis, citric acid